Cytotoxic and antibacterial evaluation of coumarins and chromanone acid from Calophyllum symingtonianum - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher; Mohamed Zulkifli, Rezauden (Journal of Applied Pharmaceutical Science, 2016)
Calophyllum symingtonianum is a rare species from the Calophyllum genus that belongs to the Guttiferae family. Calophyllum has been recognized as a potential medicinal plant due to its many bioactive phytochemicals especially coumarins and chromanone acids. In this study, the cytotoxic activities against MCF-7 and A-549 and antibacterial activities towards S. aureus, B. subtilis, P. aeruginosa and E. Coli of three coumarins known as inophyllum D, inophyllum H and calanone as well as chromanone acid identified as isocordato-oblongic acid isolated from this plant were evaluated. Inophyllum H exhibited the highest IC50 values against MCF-7 at 25.56 μg/mL and A-549 at 26.41μg/mL. Isocordato-oblongic acid showed moderate antibacterial activity against S. aureus and B. subtilis at 125μg/mL and 62.5μg/mL, respectively. This study suggests C. symingtonianum as a potential plant for cytotoxic and antibacterial phytochemicals